AloneKnight – Enabling Affective Interaction within Mobile Video Games - Jemioło, Paweł; Świder, Krzysztof; Storman, Dawid; Adrian, Weronika T. (Wydawnictwo Politechniki Łódzkiej, 2023)
Artificial intelligence is used in various contexts, including video games, where it can enhance the game design and adapt content to players’ emotional states through affective computing. In this paper, we present an example of an affective mobile game and compare participants’ opinions after playing two versions of the game, with and without an affective loop. The game was developed using Unity. In the affective version, physiological data is recorded and analysed to detect emotions based on facial expressions and electrodermal activity, which then affects the game. The study with 11 participants showed positive feedback for the game with affective loop.
Keywords: video games; mobile; artificial intelligence; affective computing; gry video; urządzenia mobilne; sztuczna inteligencja; informatyka afektywna